GEOGRAPHY TEACHERS’ ATTITUDES OF SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Mohd Zaki Said; Nor Asniza Ishak, (Journal of Contemporary Social Science and Education Studies (JOCSSES) E-ISSN- 2785-8774, 2024)
The Sustainable Development Goals (SDGs) agenda aim for another fifteen years to be achieved by 2030 since 2015, include the role of teachers to deliver SDGs elements but depends on the teachers attitude whether to believe it or not. The study focused on the attitude of Geography teachers towards the SDGs. Geography teachers show a positive attitude about the SDGs in terms of the importance of education, the role of teachers in teaching and awareness of nature, society and future generations. The finding also shows that the attitude of SDGs among option teachers is higher than non-option teachers. Geography teachers also believe in the positive effects of the SDGs on students, society and the world, but their positive views on the SDGs do not reflect teachers' practices in their Teaching and Learning (T&L) activities. This study also reflects the level of cross-curriculum elements (EMK) for teachers related to elements of Global Sustainability and Environmental Sustainability as required in Standard Based Curriculum for Secondary Schools (KSSM).